Poppies, Politics, and Power Afghanistan and the Global History of Drugs and Diplomacy - Bradford, James Tharin (Cornell University Press, 2019)
Historians have long neglected Afghanistan's broader history when portraying the opium industry. But in Poppies, Politics, and Power, James Tharin Bradford rebalances the discourse, showing that it is not the past forty years of lawlessness that makes the opium industry what it is, but the sheer breadth of the twentieth-century Afghanistan experience. Rather than byproducts of a failed contemporary system, argues Bradford, drugs, especially opium, were critical components in the formation and failure of the Afghan state.In this history of drugs and drug control in Afghanistan, Bradford shows us how the country moved from licit supply of the global opium trade to one of the major suppliers of hashish and opium through changes in drug control policy shaped largely by the outside force of the United States. Poppies, Politics, and Power breaks the conventional modes of national histories that fail to fully encapsulate the global nature of the drug trade. By providing a global history of opium within the borders of Afghanistan, Bradford demonstrates that the country's drug trade and the government's position on that trade were shaped by the global illegal market and international efforts to suppress it. By weaving together this global history of the drug trade and drug policy with the formation of the Afghan state and issues within Afghan political culture, Bradford completely recasts the current Afghan, and global, drug trade
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Jun 2021)
Keywords: Asian Studies; Diplomatic History; International Studies; HISTORY / Asia / India & South Asia; Drug control -- Afghanistan -- History; Drug traffic -- Afghanistan -- History; Opium trade -- Afghanistan -- History